The neuroprotective effect of melatonin in preventing vancomycin-induced neurotoxicity (Annals of Medical Research, 2022)
Aim: Vancomycin is a commonly used antibiotic with potent activity against Gram-positive organisms, but prolonged use and high doses can lead to toxicity. While vancomycin-associated nephrotoxicity is widely reported, few cases of neurotoxicity have been described. Presupplementation with melatonin, a powerful antioxidant for nervous tissues, protects the sciatic nerve against all of the changes. Materials and Methods: Melatonin, a neurosecretory product of the pineal gland, functions as an antioxidant in vivo and in vitro. Therefore, in this study the effect of melatonin in rats treated with vancomycin on the sciatic nerve was investigated. 28 wistar albino female rats were divided into four groups, each containing 7 rats. The first group was used as a control. The second group, melatonin (10 mg/kg/day) was injected intraperitoneally into rats for 7 days, respectively. The rats in the third group were injected with vancomycin (200 mg/kg) for 7 days, respectively. The fourth group, vancomycin (200 mg/kg)+melatonin (10 mg/kg/day) were received vancomycin for 7 days and than melatonin into rats for 7 days, respectively. The experiment was continued for 15 days. The sciatic nerve tissues were examined under light microscopes. Results: According to our findings, S100 expression was lowest in the vancomycin-treated group. In addition, the immunoreactivity intensity of S100 was significantly increased in the vancomycin+melatonin group, compared to the vancomycin group (p < 0.01). However, the immunoreactivity intensity of UCHL in the vancomycin group was no statistically significantly than the immunoreactivity intensity of UCHL in the other groups (p > 0.05).Conclusion: In this study, it was found that melatonin treatment effects positively regeneration of sciatic nerve injury caused by vancomycin in the sciatic nerve of rats.
Keywords: Neurotoxicity; Apoptosis; Pro-inflammatory; Melatonin; Oxidative stress; Vancomycin